2022
DOI: 10.1038/s41467-022-32167-6
|View full text |Cite
|
Sign up to set email alerts
|

The receptor kinase SRF3 coordinates iron-level and flagellin dependent defense and growth responses in plants

Abstract: Iron is critical for host–pathogen interactions. While pathogens seek to scavenge iron to spread, the host aims at decreasing iron availability to reduce pathogen virulence. Thus, iron sensing and homeostasis are of particular importance to prevent host infection and part of nutritional immunity. While the link between iron homeostasis and immunity pathways is well established in plants, how iron levels are sensed and integrated with immune response pathways remains unknown. Here we report a receptor kinase SR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 71 publications
3
21
0
Order By: Relevance
“…Recently, we had found that SRF3 is critical in regulating the root growth response to low iron levels and to the bacterial peptide flagellin 22 (flg22) 27 . Under both conditions SRF3 is rapidly degraded from the plasma membrane (Supplementary Data 1a) 27 . We set out to explore by which cellular mechanism SRF3 is degraded from this compartment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we had found that SRF3 is critical in regulating the root growth response to low iron levels and to the bacterial peptide flagellin 22 (flg22) 27 . Under both conditions SRF3 is rapidly degraded from the plasma membrane (Supplementary Data 1a) 27 . We set out to explore by which cellular mechanism SRF3 is degraded from this compartment.…”
Section: Resultsmentioning
confidence: 99%
“…Since we had previously demonstrated that SRF3 is at the nexus of signaling pathways that are triggered in response to low iron levels and bacterial elicitation by flg 22 27 , we wondered whether SRF3 degradation is required to mediate signaling upon both signals. We first dissected whether SRF3 regulates low iron and flg22 root growth through a common or through independent signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations